2020
DOI: 10.21203/rs.3.rs-35350/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Food Safety Knowledge among University Students in Pakistan: A Cross-Sectional Study

Abstract: Background Foodborne diseases are among the most serious public health problems and young adults are an important target group as they often engage in risky food handling practices. The purpose of this study was to assess the level of food safety knowledge and its determinants among Pakistani university students. Method A cross-sectional study was conducted among university students during the academic year 2018-2019. A convenient sample of 1417 students completed a structured questionnaire containing forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…For instance, a cross‐sectional study conducted among the students at different universities across Lahore, Pakistan, to evaluate the knowledge of food safety, foodborne disease, and general food hygiene revealed that these students had low to moderate knowledge of food safety with a mean score of (62.5 ± 8.4), with only the females, and students from health‐related backgrounds scoring significantly higher than the rest of the participants. The major predictors for this variability in overall knowledge about food safety were gender, age, academic disciplines, level of education, and father's education (Ullah et al, 2020). Similarly, another study (Naeem et al, 2018) to evaluate the knowledge about food safety, attitude toward food safety, and food handling practices of household women with varying educational backgrounds in Lahore revealed some interesting results as well.…”
Section: Food Safety and Food Fraud Scenario In Pakistanmentioning
confidence: 99%
“…For instance, a cross‐sectional study conducted among the students at different universities across Lahore, Pakistan, to evaluate the knowledge of food safety, foodborne disease, and general food hygiene revealed that these students had low to moderate knowledge of food safety with a mean score of (62.5 ± 8.4), with only the females, and students from health‐related backgrounds scoring significantly higher than the rest of the participants. The major predictors for this variability in overall knowledge about food safety were gender, age, academic disciplines, level of education, and father's education (Ullah et al, 2020). Similarly, another study (Naeem et al, 2018) to evaluate the knowledge about food safety, attitude toward food safety, and food handling practices of household women with varying educational backgrounds in Lahore revealed some interesting results as well.…”
Section: Food Safety and Food Fraud Scenario In Pakistanmentioning
confidence: 99%
“…In this regard, consumer knowledge, awareness and attitude are considered the basics that predict the level of food safety as consumer behavior is highly controlled by the current food handling procedures, food knowledge and safety, and general hygiene. 10,11 Food safety and quality are two of the most important concerns of any university, and this makes a lot of sense given the fact that any university may have tens of thousands of students and staff. 12 Studies evaluating food safety knowledge are important for an efficient and integrated food safety education program, and are important for responsible authorities to develop food safety policies.…”
Section: Introductionmentioning
confidence: 99%